Market and Business in the Educational Field: Representations of Authority in the Documents of the Dirección General de Cultura y Educación (2015–2019) (Praxis Educativa, 2025)
This study explores the social representations of authority in the documents of the General Directorate of Culture and Education of the Province of Buenos Aires published between 2015 and 2019. A total of 19 documents were selected based on two criteria: (1) that they mention authority relationships in schools; (2) that they were produced during the administration of the Cambiemos coalition. The meaning of the term “ideology” is defined, and the relationships between social representations and ideology are examined. The political ideas that Pro–Cambiemos brought to government, their ideological roots, and their projection in political discourse on education are described. Finally, an interpretive analysis of the selected documents is conducted, exploring social representations of authority. The results reveal the presence of a central metaphor that frames authority as leadership, shifting its meaning into a discursive field centered on efficiency, control, measurement and evaluation, competition, supply and demand, entrepreneurship, individualism, performance, pragmatism, the instrumentalization of human relationships, and the absence of politics.
Keywords: social representations; authority; documents; Cambiemos; leadership